UJI RESISTENSI KLON-KLON INTRODUKSI TERHADAP PENYAKIT GUGUR DAUN Pestalotiopsis sp. DI LABORATORIUM - Sayurandi Sayurandi; Didi Kusnedy Kusnedy; Eka Bobby Febrianto; Cici Indriani Dalimunthe (Institut Teknologi Sawit Indonesia, 2021)
The rubber plant (Hevea brasiliensis) comes from Brazil. The first rubber tree grew only in South America. Rubber plantations in Indonesia were introduced in 1864, since Hofland established a rubber plantation company in Tanah Panunukan and Ciasem, West Java. Attacks caused by Pestalotiopsis sp. showed brown spots on rubber leaves and a clear boundary between the spots and the healthy leaves. Infected leaves fall prematurely. Generally, those that are heavily attacked are rubber plants that have produced and are not maintained. The aim of the study was to determine the resistance level of introduced clones (PB 217, PB 260, PB 330, PB 340, RRIC 100, IRR 220 and GT 1) to leaf fall disease, namely Pestalotiopsis sp. The research was conducted at the Plant Protection Laboratory of the Sungai Putih Research Institute, using a non-factorial Completely Randomized Design (CRD). The observation result showed that clones PB 217 and GT 1 had the highest attack intensity after 8 days of inoculation namely 89.96% and 89.96%. The lowest attack intensity was found on clone IRR 220 namely 81.64%.